2015
DOI: 10.1111/bcp.12718
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the role of community pharmacies in improving the transition from secondary to primary care

Abstract: Aim We set out to determine the potential contribution of community pharmacists to improve the transfer of care of patients from secondary to primary care settings. Method We systematically reviewed the literature on interventions that involved community pharmacy post‐discharge. We considered all relevant studies, including both randomized and non‐randomized controlled trials, irrespective of patient population. Our primary outcome was any impact on patient and medication outcomes, while the secondary outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 35 publications
(118 reference statements)
1
59
0
7
Order By: Relevance
“…This report is timely in the context of a recently published systematic review of studies evaluating the role of community pharmacists in the transition of patients from secondary to primary care [8]. In this study, community pharmacists held positive opinions of the dMUR service and could see the benefit to patients regarding identification of medicine nonadherence and avoidance of medicine errors.…”
Section: Discussionmentioning
confidence: 84%
“…This report is timely in the context of a recently published systematic review of studies evaluating the role of community pharmacists in the transition of patients from secondary to primary care [8]. In this study, community pharmacists held positive opinions of the dMUR service and could see the benefit to patients regarding identification of medicine nonadherence and avoidance of medicine errors.…”
Section: Discussionmentioning
confidence: 84%
“…A recent systematic review highlighted how community pharmacists could help identify and rectify medication errors, thus providing a significant impact on improving outcomes . In 2012, the Royal Pharmaceutical Society (RPS) issued professional guidance in its publication “Keeping patients safe when they transfer between care providers—getting the medicines right” on the core principles that underpin the safe transfer of information related to medicines for a patient transferring between care providers in any setting…”
Section: Resultsmentioning
confidence: 99%
“…95 A recent systematic review highlighted how community pharmacists could help identify and rectify medication errors, thus providing a significant impact on improving outcomes. 96 In 2012, the Royal Pharmaceutical Society (RPS) issued professional guidance in its publication "Keeping patients safe when they transfer between care providers-getting the medicines right" on the core principles that underpin the safe transfer of information related to medicines for a patient transferring between care providers in any setting. 97 Effective interventions for minimizing medication interactions and keeping patients out of hospital have long been shown to be cost-effective, with the PINCER trial evidencing important reductions in medication misuse in various therapeutic areas, including antihypertensive medication.…”
Section: Secondary Care For Episodes Of Ill Healthmentioning
confidence: 99%
“…9 Furthermore, community pharmacists often develop longlasting therapeutic relationships with their patients, and they have shown increased potential to address many population health issues, such as medication-related issues during transitions in care. 10 Nazar et al 11 recently examined the impact of community pharmacists on transitions of care and found that community pharmacists can reduce the incidence of drug-related problems after discharge; however, they did not quantify the impact of community pharmacists on transitions of care. Herein, we report our findings following a systematic review of the literature of community pharmacist interventions on patients transitioning from hospital to home on 30-day readmissions, a primary outcome of patients following discharge.…”
Section: Introductionmentioning
confidence: 99%